1997
DOI: 10.1159/000291495
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of the Serum Uric Acid Level Preceding the Clinical Manifestation of Preeclampsia in Twin Pregnancies

Abstract: To assess changes in the serum uric acid level in the third trimester of twin pregnancies, a total of 152 consecutive women with twin pregnancies were examined. Serum uric acid levels were analyzed in the women at varying gestational weeks in the presence or absence of preeclampsia. A receiver operating characteristic curve was used to determine the optimal cutoff value of serum uric acid between 30 and 31 weeks of gestation predicting subsequent development of preeclampsia. Forty-four women (29%) developed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…UA was found to protect significantly against oxidative stress and to scavenge toxic reactants, particularly peroxynitrite (ONOO À ), a potent oxidant that is formed by the rapid combination of the free radical nitric oxide with superoxide. 2 In agreement with our findings, increased UA levels have been reported by Koike et al 21 in pre-eclamptic patients. Some authors have also suggested a correlation between high serum UA and severity of disease.…”
Section: Discussionsupporting
confidence: 93%
“…UA was found to protect significantly against oxidative stress and to scavenge toxic reactants, particularly peroxynitrite (ONOO À ), a potent oxidant that is formed by the rapid combination of the free radical nitric oxide with superoxide. 2 In agreement with our findings, increased UA levels have been reported by Koike et al 21 in pre-eclamptic patients. Some authors have also suggested a correlation between high serum UA and severity of disease.…”
Section: Discussionsupporting
confidence: 93%
“…6.8 mg/dl and 6.3 mg/dl respectively-when compared with values in chronic essential hypertension with pregnancy (5.7 mg/dl). [22][23][24][25][26][27][28] Out of 100 cases, there were 20 preterm baby and others such as stillbirth and IUD. So, these entire abnormal fetal outcomes were in the hyperuricaemic group and 5.3 times higher as compared to low serum uric acid group.…”
Section: Discussionmentioning
confidence: 99%
“…hypoxanthine; adenosine; uric acid; twin pregnancy © 2004 Tohoku University Medical Press An association between twin pregnancy and elevated maternal serum uric acid levels has been noted (Fischer et al 1995;Koike et al 1997). Some possible mechanisms leading to this consequence have been discussed (Fischer et al 1995;Koike et al 1997).…”
Section: Suzuki S and Yoneyama Y Maternal Plasma Hypoxanthine Levmentioning
confidence: 99%
“…Some possible mechanisms leading to this consequence have been discussed (Fischer et al 1995;Koike et al 1997). Fischer et al (2001) reported that maternal hyperuricemia during the third trimester of nonpreeclamptic twin pregnancies is in part due to increased uric acid production.…”
Section: Suzuki S and Yoneyama Y Maternal Plasma Hypoxanthine Levmentioning
confidence: 99%